The The Integration of Word Wall Media to Improve EFL Students’ Vocabulary Mastery at Junior High School Pulau Morotai - Megawati Basri; Dwi Budidarma Sutrisno (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to investigate the effect of word wall media on students’ vocabulary acquisition in English at Junior High School. It can be a practical and effective strategy for educators to enhance students’ vocabulary acquisition in English, as it provides visual reinforcement and promotes active engagement with new words in the classroom.  The study employed a mixed-methods approach, combining a quasi-experimental design with qualitative interviews—the number of participants of this study (N=40, 20 per group). The experimental group’s vocabulary scores significantly improved from a pretest mean of 30.95 to a posttest mean of 51.60. The control group, on the other hand, which employed conventional methods, showed only a slight improvement, from 39.00 to 40.15. An independent sample t-test confirmed a statistically significant difference between the two groups (t (38) =-4.170, p<.001), with a mean difference of -20.650 and a 95% confidence interval of -30.675 to -10.625. According to Levene’s test, equal variances were met (p=.139), ensuring the validity of the analysis. The qualitative data, analyzed thematically, supported the quantitative findings. Student interviews revealed two main themes: (1) increased multimodal learning awareness, and (2) enhanced motivation driven by the gamification features of the word wall. Students reported higher engagement and enthusiasm during the learning session that incorporated the word wall media. In conclusion, the integration of word wall media significantly improves vocabulary acquisition and supports active, motivated learning. These findings suggest that word walls are a useful and engaging teaching tool for vocabulary in English classroom.